Incidence of Malnutrion Based On Body Mass Index And Subjective Global Assesment In Patients With Stable Chronic Obstructive Pulmonary Disease - Muhammad Bayhaqi Dalimunthe; Andika Pradana; Amira Permatasari Tarigan; Rina Amelia (CV. Inara, 2025)
Background: Malnutrition is a serious problem in patients with COPD, it interferes with normal skeletal muscle function, with reduced muscle mass and decreased respiratory muscle strength and endurance. The purpose of the study was to determine the incidence of malnutrition based on BMI and SGA in patients with stable chronic obstructive pulmonary disease at the Prof. Dr. Chairuddin P. Lubis Medan Teaching Hospital. Method: The research design is an observational analytic, from November 2023 to March 2024. The study population was COPD patients who sought treatment at the Pulmonary Polyclinic at RSCPL with a total sample using the consecutive sampling method of 91 people Assessment of BMI by measuring TB and BW of patients when they came and assessment of SGA with a questionnaire Data processing using SPSS using descriptive statistics by displaying the IMT and SGA frequency distribution tables. Result: The results of this study found that most patients were categorized as underweight, namely 28 patients (30.8%). The majority of SGA classification as underweight/moderate nutrition